2017
DOI: 10.1093/rheumatology/kex324
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the EULAR definition of arthralgia suspicious for progression to rheumatoid arthritis

Abstract: The EULAR definition of arthralgia suspicious for progression to RA is sensitive when used to support the rheumatologist's opinion on imminent RA. This validation study shows that the definition, when used as designed, further homogenizes patients that rheumatologists consider at risk for RA. To arrive at a high specificity, the clinical definition needs to be combined with biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 10 publications
3
33
0
1
Order By: Relevance
“…74% of patients with CSA had a positive EULAR definition. 19 CSA, clinically suspect arthralgia; GP, general practitioner; EULAR, European League Against Rheumatism; RA, rheumatoid arthritis; MSK, musculoskeletal symptoms.…”
Section: Differentiating Arthralgia Suspicious For Progression To Ra mentioning
confidence: 99%
See 1 more Smart Citation
“…74% of patients with CSA had a positive EULAR definition. 19 CSA, clinically suspect arthralgia; GP, general practitioner; EULAR, European League Against Rheumatism; RA, rheumatoid arthritis; MSK, musculoskeletal symptoms.…”
Section: Differentiating Arthralgia Suspicious For Progression To Ra mentioning
confidence: 99%
“…The first longitudinal study of patients with CSA showed that the definition had a high sensitivity and served to further harmonise patients, as patients with arthralgia who were identified as CSA by their rheumatologist but had <3 clinical items indeed had a lower risk of progression to RA. 19 …”
Section: Differentiating Arthralgia Suspicious For Progression To Ra mentioning
confidence: 99%
“…A combination of clinical symptoms and signs suggestive of future RA has been developed, resulting in the EULAR definition of arthralgia suspicious for progression to RA 23. The clinical definition has shown to be highly sensitive when tested against the external standard ‘expert diagnosis of RA’ in cross-sectional studies and actual RA development in longitudinal studies 23 24. In order to obtain a sufficiently high specificity, the clinical definition should be combined with the results of biomarkers.…”
Section: Identifying Persons With Arthralgia At Risk For Ramentioning
confidence: 99%
“…2). 8,9 In a healthy person, the genetic risk factors, the environmental risk factor of smoking, and the presence of autoantibodies are insufficient to detect early disease. The genetic risk factors are very common, and actually everyone carries one or several of the risk alleles.…”
Section: Clinical Background: Early Disease Detectionmentioning
confidence: 99%